Smuggled or Trafficked? Refugee or job seeker? Deconstructing rigid classifications by rethinking women’s vulnerability - Serughetti, Giorgia (Anti-Trafficking Review, 2018)
In the context of recent large-scale migratory flows from North Africa to the European Union, significant convergence and overlap has been observed between human trafficking and migrant smuggling, and between ‘economic’ and ‘forced’ migration. This paper draws on the case of Nigerian women asylum seekers, most of whom are identified as potential victims of human trafficking, to illustrate the problems that arise when migrants are separated into discrete categories—trafficked/smuggled, voluntary/forced—to establish their treatment. These problems derive from the application of rigid bureaucratic labels to increasingly fluid migratory identities, and from gendered and neo-colonial stereotypes that inform views of agency and vulnerability. The paper discusses vulnerability as a core concept in the construction of the ‘deserving victim’ in order to critique stereotypical representations of ‘vulnerable subjects’ in light of feminist political philosophy and philosophy of law. In doing so, it highlights the role of receiving states in producing migrant women’s vulnerability, and argues that state institutions have a duty to both guarantee protection and acknowledge the subjects’ agency.